Barramento de Comunicação IoT para Plataforma de Pecuária de Precisão - Willyan Candido Silva (2021)
Brazilian cattle breeding has demonstrated over the years its primacy in the world beef market. As a result of this situation and its importance for the country’s economic sector, developing and improving the means used in the beef cattle production chain is crucial to increase production, reduce costs and ensure the constant progress required by the market. In this context, the use of an infrastructure based on the Internet of Things (IoT) contributes to low-cost monitoring and provides the opportunity to automate beef-producing properties. FACOM / UFMS and Embrapa Gado de Corte have several researches and projects aimed at precision cattle breeding, among them the e-Cattle platform. The objective of this work is to provide a communication bus with IoT protocols for the integration of a greater variety of sensors and the persistence of information collected on the platform. Thus, the use of IoT communication protocols, as for example LoRA and MQTT, will increase the heterogeneity of accepted sensors, contributing to a low-cost implementation and monitoring solution.